Principal Leadership Strategies and Parental Involvement in Elementary School Learning - Azizah Azizah; Marwan Marwan; Siraj Siraj (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
Parental involvement is crucial to improve the quality of learning at the primary school level, yet it is often restricted and unequal. This study investigates the tactics used by school administrators to increase family participation in the learning process, assesses the efficiency of various leadership strategies in establishing school-parent synergy, and analyses the challenges associated with increasing parental involvement. Data were obtained from elementary schools in Cluster 4, Pidie Regency, using a qualitative field study design that included observations, in-depth interviews, and document analysis. The data show that administrators have used a variety of tactics, including routine communication, family involvement in school events, and the availability of collaboration spaces. These methods are positive, but they have not yet resulted in optimal and equitable parental participation. The effectiveness of leadership methods in developing synergy between schools and parents is still in its early stages, with modest impact on long-term parental support and student learning outcomes. Low parental awareness, work-related time restrictions, a lack of knowledge of parental obligations, and poor two-way communication are all significant barriers. The study finds that increasing parental involvement necessitates more tailored, consistent, and educational leadership tactics. The findings add to the conversation about educational leadership by emphasizing the significance of contextualized principal tactics in developing school-parent partnerships at the primary level